2016
DOI: 10.1016/j.clbc.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy and Trastuzumab Is Safe and Effective in Older Women With Small, Node-Negative, HER2-Positive Early-Stage Breast Cancer

Abstract: The benefit of adjuvant trastuzumab with chemotherapy in breast cancer is well-established; however, its impact on outcomes for older women with small, node-negative, human epidermal growth factor receptor 2-positive disease is less clear and unlikely to be addressed in prospective studies. This retrospective, sequential cohort study suggests adjuvant trastuzumab with chemotherapy results in excellent breast cancer outcomes with few cardiac events in this population. Introduction The benefit of adjuvant trast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…A recent study from India showed a substantial increase of HER2-targeted therapy among patients treated at a public hospital in the past decade, likely due to the advent of biosimilars, the use of shorter duration adjuvant regimens [ 21 ]. Another study by Cadoo et al [ 22 ] has shown the efficacy of adjuvant chemotherapy and trastuzumab in elderly patients. However, the patient cohort in this study was age >55 years and <25% of the patients were above 70 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from India showed a substantial increase of HER2-targeted therapy among patients treated at a public hospital in the past decade, likely due to the advent of biosimilars, the use of shorter duration adjuvant regimens [ 21 ]. Another study by Cadoo et al [ 22 ] has shown the efficacy of adjuvant chemotherapy and trastuzumab in elderly patients. However, the patient cohort in this study was age >55 years and <25% of the patients were above 70 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…La terapia antiHER2 se ha asociado además con toxicidad cardiaca, sin embargo la frecuencia de esta puede variar [31]. Un estudio hecho en pacientes mayores, muestra que la adición de trastuzumab a la quimioterapia adyuvante, se puede relacionar con una baja incidencia de eventos cardiacos, una supervivencia general a 4 años del 99% y una supervivencia libre de recaídas a distancia del 99% [32]. Entre nuestras pacientes no se reportó suspensión de la terapia debido a efectos cardiotóxicos del trastuzumab.…”
Section: Discussionunclassified
“…Nevertheless, the results of this meta-analysis may have contributed to the lower use of adjuvant chemotherapy in older BC patients [35]. Other recent studies suggest a possible benefit from adjuvant chemotherapy in older BC patients, especially in those with HER2-positive disease [37,38]. Recently, Du et al compared the effectiveness of adjuvant chemotherapy between older BC and CRC patients, and found that chemotherapy might be effective in BC patients up to the age of 79 years [39].…”
Section: Discussionmentioning
confidence: 99%